MODEL TAFSIR INTEGRATIF; STUDI AL-QUR’AN KONTEKSTUAL, REFLEKTIF DAN ETIS - Muhammad Zulkarnain Mubhar; Imam Zarkasyi Mubhar (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2026)
This study explores the development of Qur’anic exegesis across three major phases: classical, modern, and contemporary. Using a qualitative-descriptive approach and critical hermeneutics, the article compares the epistemological orientations and socio-political responses of each exegetical model concerning key issues such as gender justice, jihad, and ecological crisis. The findings reveal that classical tafsir emphasizes the preservation of traditional authority, modern tafsir focuses on rationality and moral reform, while contemporary tafsir advocates critical reconstruction and sensitivity to global contexts. This study proposes an integrative model of interpretation that synthesizes the strengths of all three approaches to meet present-day challenges ethically and meaningfully. It positions Qur’anic exegesis not only as an intellectual discourse but also as a transformative and liberative practice.